Preparation method and application of nitrogen-doped graphite electro-ozonation cathode
By preparing nitrogen-doped graphite electrodes, the problem of low efficiency in the two-electron oxygen reduction reaction of carbon-based materials was solved, realizing efficient H2O2 generation and dye wastewater degradation in the electro-ozone process, which is suitable for large-scale water pollution treatment.
Patent Information
- Application Number
- CN202511621351.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-07
- Publication Date
- 2026-01-09
AI Technical Summary
Existing carbon-based materials have low efficiency in the two-electron oxygen reduction reaction in the electro-ozone process, making it difficult to replace precious metal catalysts. Furthermore, commercially available carbon materials are not suitable for H2O2 generation, resulting in insufficient efficiency of the electro-ozone process in treating pollutants.
Nitrogen-doped graphite electrodes were prepared by electrochemical oxidation and melamine pyrolysis, forming a rich porous structure and uniform nitrogen doping, which enhanced the oxygen reduction reaction activity, making it suitable as a cathode material for the electro-ozone process.
The prepared nitrogen-doped graphite electrode exhibits excellent H2O2 generation performance in the electro-ozone process, which can efficiently degrade dye wastewater, especially under high-salt conditions, and has the potential for large-scale application.
Smart Images

Figure CN121292587A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of water pollution treatment, and particularly relates to a preparation method and application of a nitrogen-doped graphite electro-peroxone cathode. BACKGROUND
[0002] The electro-peroxone (E-peroxone) process is a new electrochemical advanced oxidation process (EAOP), which combines ozone oxidation and in-situ cathodic hydrogen peroxide production to generate a large amount of hydroxyl radicals with strong oxidizing properties, which synergistically catalyze the oxidation and degradation of organic matter. The electro-peroxone technology makes up for the shortcomings of traditional advanced oxidation technologies, and in the past few years, the electro-peroxone process has become one of the most promising choices for wastewater treatment. In the electro-peroxone reaction system, pure O2 is introduced into an ozone generator to generate O3, and the mixed gas containing O3 and O2 is sprayed onto the cathode in the electrochemical reactor through the aeration head, O2 is reduced to produce H2O2 at the cathode, and then reacts with O3 to generate a large amount of •OH to degrade organic matter. Therefore, the selection of a cathode material capable of efficiently generating H2O2 is crucial for realizing the synergistic effect of peroxides on pollutant degradation.
[0003] Among two-electron oxygen reduction reaction catalysts, noble metals and their alloys (such as Pd, Au, Pd-Au, etc.) are currently the most efficient catalysts, but due to the high cost and scarcity of noble metals, it is difficult to achieve large-scale application. Carbon-based materials have low price, wide source, easy conductivity, corrosion resistance, high hydrogen evolution overpotential, and unique surface and structural properties that can be fine-tuned, and are considered to be good substitutes for noble metal catalysts in the electrochemical synthesis of H2O2. However, the two-electron oxygen reduction reaction of commercial carbon materials (such as carbon felt, mesh-like glassy carbon) is poor, which is not conducive to the generation of H2O2. N-doping can easily change the atomic structure and electron distribution of the carbon skeleton, which is due to the high electronegativity of nitrogen (3.04). The introduction of nitrogen elements into carbon materials will cause the transfer of electrons on carbon to nitrogen, thereby generating a partial positive charge on the carbon atoms, which can promote the interaction between the catalyst and O2 and the adsorption of O2 on the carbon material, enhancing its catalytic activity. Therefore, there is a need in the art to prepare a nitrogen-doped graphite cathode material that has high efficiency in treating target pollutants, is simple to prepare, and has large-scale application potential. SUMMARY
[0004] In view of the problems in the prior art, the application provides a preparation method and application of a nitrogen-doped graphite electro-peroxone cathode. The nitrogen-doped graphite cathode prepared by the application has a rich pore structure, the nitrogen doping is uniformly and stably dispersed, and exhibits excellent electrocatalytic oxygen reduction performance to generate hydrogen peroxide, and has good application potential in the field of electro-peroxone technology for treating dye wastewater.
[0005] The preparation method of the nitrogen-doped graphite electrode of the present application is carried out in the following steps:
[0006] (1) The graphite felt material is pretreated and cleaned to remove grease and dirt on the surface of the graphite felt material;
[0007] (2) The graphite material is electrochemically oxidized with 0.05 mol / L sodium sulfate solution as the electrolyte, graphite plate as the cathode and graphite felt as the anode to obtain an oxidized graphite felt cathode rich in oxygen-containing functional groups;
[0008] (3) The treated oxidized graphite felt is ultrasonically immersed in a melamine, water and ethanol mixed solution to obtain melamine-attached oxidized graphite felt and dry it;
[0009] (4) The melamine-attached oxidized graphite felt is placed in a tube furnace and subjected to programmed temperature pyrolysis in a nitrogen atmosphere to obtain a nitrogen-doped graphite electrode.
[0010] In the present application, the electrochemical oxidation conditions in (2) are 0.1 A current for 10 min.
[0011] In the present application, the concentration of the melamine mixed solution in (3) is 1 g / ml, and the volume ratio of water to ethanol is 1:1.
[0012] In the present application, the ultrasonic immersion time of the oxidized graphite felt in the mixed solution in (3) is 0.5-5 min.
[0013] In the present application, the calcination conditions in (4) are to heat to 600-800℃ at a rate of 3.3 min / ℃ in the tube furnace, and the holding time is 0.5-3 h.
[0014] The electrode prepared by the above method is applied in electro-peroxone technology, and the nitrogen-doped graphite electrode is used as the cathode in the electro-peroxone system.
[0015] In the above application, the nitrogen-doped graphite electrode is used as the cathode material, and the graphite plate is used as the anode material.
[0016] In the above application, the temperature is room temperature, the pH is 3-11, the simulated wastewater salt concentration is 0.05-0.6 mol / L, and the main components are sodium sulfate, sodium chloride and their mixed solutions.
[0017] Compared with the prior art, the present application has at least the following beneficial effects:
[0018] 1. This invention uses a tube furnace pyrolysis method to perform nitrogen doping, resulting in a nitrogen-doped graphite electrode with a rich porous structure, uniform and stable nitrogen doping dispersion, and excellent electrocatalytic oxygen reduction to hydrogen peroxide production performance. The preparation method is simple to operate, the raw materials are inexpensive and readily available, and it has the potential for large-scale application.
[0019] 2. Before nitrogen doping, the graphite felt material is electrochemically modified by increasing the oxygen-containing functional groups on its surface through anodic oxidation, thereby increasing the active sites for oxygen reduction reactions.
[0020] 3. The prepared electrode has a wide range of applications in the electro-ozone technology for degrading dye wastewater, and still has excellent degradation effect under high salinity conditions. Attached Figure Description
[0021] Figure 1 shows the SEM image of the nitrogen-doped graphite electrode;
[0022] Figure 2 shows a comparison of the electro-ozone degradation of dyes using nitrogen-doped graphite electrodes and non-nitrogen-doped graphite electrodes.
[0023] Figure 3 shows a comparison of the electro-ozone degradation of dyes by nitrogen-doped graphite electrodes under different sodium sulfate concentrations.
[0024] Figure 4 shows a comparison of the electro-ozone degradation of dyes by nitrogen-doped graphite electrodes under different sodium chloride concentrations.
[0025] Figure 5 shows a comparison of the electro-ozone degradation of dyes by nitrogen-doped graphite electrodes under different concentrations of sodium sulfate and sodium chloride.
[0026] Figure 6 shows the nitrogen-doped graphite electrode after being repeatedly used 5 times for electro-ozone degradation of dye. Detailed Implementation
[0027] The following examples further illustrate the method and effects of the present invention in detail. These examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following examples.
[0028] Example 1
[0029] In this embodiment, the nitrogen-doped graphite electrode is prepared by the following steps:
[0030] (1) Cut a graphite felt with a size of 3×5cm, and clean it with ethanol for 15min three times and deionized water for 15min three times to remove grease and dirt from the surface of the graphite felt material.
[0031] (2) Using 0.05 mol / L sodium sulfate solution as electrolyte, graphite plate as cathode, graphite felt as anode, and working current set to 0.1 A, graphite felt material was obtained after energizing for 10 min;
[0032] (3) The treated graphite oxide felt was ultrasonically immersed in a mixed solution of melamine, water and ethanol for 1 min. The concentration of the melamine mixed solution was 1 g / mL and the volume ratio of water and ethanol was 1:1. The resulting graphite oxide felt with melamine adhering was then dried.
[0033] (4) Place the melamine-attached graphite felt in a tube furnace and heat it to 700°C at a rate of 3.3 min / °C. Hold it for 1 h to obtain nitrogen-doped graphite electrode material, denoted as NE700-1min-1h.
[0034] The prepared NE700-1min-1h was used for electro-ozone degradation of dye wastewater. The specific operation steps are as follows:
[0035] (1) Prepare simulated dye wastewater, select Acid Red B as the target dye, sodium sulfate as the supporting electrolyte, the concentration of Acid Red B is 50 mg / L, and the concentration of electrolyte is 0.05 mol / L;
[0036] (2) Use NE700-1min-1h as the cathode and graphite plate as the anode. The flow rate of O3 / O2 mixed gas is 100mL / min and the current is 0.1A. Sample the simulated wastewater at regular intervals until the water sample becomes colorless.
[0037] (3) The concentration of Acid Red B was determined by ultraviolet spectrophotometry.
[0038] Example 2
[0039] Same as Example 1, except that: (4) the melamine-attached graphite felt is placed in a tube furnace and heated to 600°C at a rate of 3.3 min / °C and held for 1 h to obtain nitrogen-doped graphite electrode material, denoted as NE600-1min-1h.
[0040] Example 3
[0041] Same as Example 1, except that: (4) the melamine-attached graphite felt is placed in a tube furnace and heated to 800°C at a rate of 3.3 min / °C, and held for 1 h to obtain nitrogen-doped graphite electrode material, denoted as NE800-1min-1h.
[0042] Example 4
[0043] Same as Example 1, except that: (4) the melamine-attached graphite felt was placed in a tube furnace and heated to 700°C at a rate of 3.3 min / °C and held for 2 h to obtain nitrogen-doped graphite electrode material, denoted as NE700-1min-2h.
[0044] Comparative Example 1
[0045] Compared to Example 1, Comparative Example 1 prepared a nitrogen-free graphite electrode using the following steps:
[0046] (1) Cut a graphite felt with a size of 3×5cm, and clean it with ethanol for 15min three times and deionized water for 15min three times to remove grease and dirt from the surface of the graphite felt material.
[0047] (2) Using 0.05 mol / L sodium sulfate solution as electrolyte, graphite plate as cathode, graphite felt as anode, and working current set to 0.1 A, graphite felt material was obtained after energizing for 10 min, denoted as EGF.
[0048] The prepared EGF was used for electro-ozonation degradation of dye wastewater. The specific operation steps are as follows:
[0049] (1) Prepare simulated dye wastewater, select Acid Red B as the target dye, sodium sulfate as the supporting electrolyte, the concentration of Acid Red B is 50 mg / L, and the concentration of electrolyte is 0.05 mol / L;
[0050] (2) Use NE700-1min-2h as the cathode and graphite plate as the anode. The flow rate of O3 / O2 mixed gas is 100mL / min and the current is 0.1A. Sample the simulated wastewater at regular intervals until the water sample becomes colorless.
[0051] (3) The concentration of Acid Red B was determined by ultraviolet spectrophotometry.
[0052] The effects of NE700-1min-1h, NE600-1min-1h, NE800-1min-1h, and EGF prepared in Examples 1, 2, and 3, as well as Comparative Example 1, on the degradation of dye wastewater by electro-ozone were investigated. The changes in Acid Red B concentration over degradation time are shown in the graph below. Figure 3 As shown, from Figure 3As can be seen, the degradation performance of Acid Red B by NE700-1min-1h, NE600-1min-1h, and NE800-1min-1h is higher than that of EGF. Among them, the degradation rate of NE700-1min-1h reaches 96.1% after 10 min, the degradation rate of NE600-1min-1h reaches 94.6% after 10 min, and the degradation rate of NE800-1min-1h reaches 88.4% after 10 min, which is much higher than that of EGF (83.0% degradation rate after 10 min).
[0053] The NE700-1min-2h reactor prepared in Example 4 was used as the cathode to investigate its ability to electro-ozone degrade dye wastewater under different salt concentrations. Acid Red B was selected as the target dye for the simulated dye wastewater, with a concentration of 50 mg / L. The solutions were sodium sulfate solution, sodium chloride solution, and a mixture of both salts. The NE700-1min-2h reactor was used as the cathode, and a graphite plate as the anode. The O3 / O2 mixed gas flow rate was 100 mL / min, and the current was 0.1 A. Samples of the simulated wastewater were taken at regular intervals until the water sample became colorless. The resulting graph shows the change in Acid Red B concentration over degradation time. Figure 4 , Figure 5 and Figure 6 As shown.
[0054] from Figure 4 As can be seen, when the degradation time is 20 min, the degradation rates of simulated dye wastewater with sodium sulfate solution concentrations of 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, and 0.6 mol / L are 98.8%, 98.7%, 95.2%, 94.9%, and 93.6%, respectively. Compared with a concentration of 0.05 mol / L, the degradation rates at concentrations of 0.2 mol / L, 0.4 mol / L, and 0.6 mol / L decrease by 0.1%, 3.64%, 3.9%, and 5.3%, respectively. With increasing salt concentration, the degradation performance of Acid Red B decreases, but the decrease is relatively small. Figure 5 As can be seen, the degradation performance of Acid Red B actually increases with the increase of sodium chloride solution concentration. When the degradation time is 10 min, the degradation rate of simulated dye wastewater with different sodium chloride concentrations all reach more than 97.5%. Figure 6 A 1:1 mixture of sodium sulfate and sodium chloride was used. It can be seen that the degradation performance of Acid Red B exhibits a peak as the concentration of the mixed solution increases, but the change is relatively small. Even at a total salt ion concentration of 0.4 mol / L, the degradation rate still reaches 99% after 20 minutes. In summary, the NE700-1min-2h electrode still demonstrates excellent ability to degrade target pollutants under high-salt conditions.
[0055] The NE700-1min-2h reactor prepared in Example 4 was used as the cathode to investigate its reusability stability in the electro-ozone system for degrading dye wastewater. Simulated dye wastewater was prepared, with Acid Red B selected as the target dye, sodium sulfate as the supporting electrolyte, an Acid Red B concentration of 50 mg / L, and an electrolyte concentration of 0.05 mol / L. The NE700-1min-2h reactor was used as the cathode, a graphite plate as the anode, an O3 / O2 mixed gas flow rate of 100 mL / min, and a current of 0.1 A. Samples of the simulated wastewater were taken at regular intervals until the water sample became colorless. This process was repeated 5 times, and the change in Acid Red B concentration over degradation time is shown in the graph below. Figure 6 As shown, the NE700-1min-2h electrode exhibits good stability.
[0056] The above description is only a preferred embodiment of the present invention. The size of the graphite felt can be from 2×2 cm to 10×10 cm, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or changes made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a nitrogen-doped graphite electro-ozone cathode, characterized in that, Includes the following steps: (1) Pre-treat and clean the graphite felt material to remove grease and dirt from the surface of the graphite felt material; (2) Using sodium sulfate solution as electrolyte, graphite plate as cathode and graphite felt as anode, graphite material is electrochemically oxidized to obtain graphite felt cathode rich in oxygen-containing functional groups. (3) The treated graphite oxide felt was ultrasonically immersed in a mixed solution of melamine, water and ethanol to obtain melamine-attached graphite oxide felt and then dried. (4) Place the melamine-coated graphite felt in a tube furnace and perform programmed temperature pyrolysis in a nitrogen atmosphere to obtain nitrogen-doped graphite electrodes.
2. The method for preparing a nitrogen-doped graphite electro-ozone cathode according to claim 1, characterized in that: (2) The electrochemical oxidation conditions described are 0.1 A current for 10 min.
3. The method for preparing a nitrogen-doped carbon electrode-ozone cathode according to claim 1, characterized in that: (3) The concentration of the melamine mixed solution is 1 g, and the volume ratio of water to ethanol is 1:
1.
4. The method for preparing a nitrogen-doped graphite electro-ozone cathode according to claim 1, characterized in that: (3) The ultrasonic soaking time of the graphite felt in the mixed solution is 0.5~5 min.
5. The method for preparing a nitrogen-doped graphite electro-ozone cathode according to claim 1, characterized in that: (4) The calcination conditions are to heat to 500~800℃ in a tube furnace at a rate of 3.3 min / ℃ and hold for 0.5~3 h.
6. A nitrogen-doped graphite electro-ozone cathode prepared by any one of the preparation methods according to claims 1 to 5.
7. The application of the electrode according to claim 6 in electro-ozone technology, characterized in that... Nitrogen-doped graphite electrode was used as the cathode.
8. The application of the electrode according to claim 6 in electro-ozone technology, characterized in that... The reaction temperature is room temperature, the pH is 3~11, the salt concentration of the wastewater is 0.05~0.6 mol / L, and the main components are sulfate, chloride and their mixed solutions.